Guide to prevention of inadvertent ignition of flamemable atmospheres by radio-frequency radiation (BSI, 1986)
Radio-wave hazards, Radio waves, Radiofrequencies, Electromagnetic radiation, Radiation protection, Fire safety, Fire risks, Flammable atmospheres, Flammable materials, Explosive atmospheres, Ignition, Electric sparks, Transmitters, Radio transmitters, Radar transmitters, Field strength (electric), Radius, Antennas, Television transmitters, Communication equipment, Electronic equipment and components, Electrical wave measurement, Field testing, Electric discharges, Safety measures, Fire tests, Test equipment, Mathematical calculations, Bibliography, Power output, Electromagnetic fields